Elevated semaphorin5A in systemic lupus erythematosus is in association with disease activity and lupus nephritis. (17th February 2017) - Du, Y.; Wu, X.; Chen, M.; Wang, W.; Xv, W.; Ye, L.; Wu, D.; Xue, J.; Sun, W.; Luo, J.; Wu, H.
Summary: Systemic lupus erythematosus (SLE) is an autoimmune disease characterized by extensive immune response, including over‐activation of T and B cell development of pathogenic autoantibodies, organ damage induced by the formation and deposition of immune complex and the abnormal elevation of type I interferon. Semaphorin5A (Sema5A) is involved essentially in immune cell regulation and is also implicated in the pathogenesis of autoimmune disorders. We aimed to evaluate the role of Sema5A in patients with SLE. Serum levels of Sema5A were tested by enzyme‐linked immunosorbent assay (ELISA) in 152 SLE patients and 48 healthy controls. The message ribonucleic acid (mRNA) expression levels of Sema5A and ADAM metallopeptidase domain 17 (ADAM17) in the peripheral blood mononuclear cells (PBMC) from 43 patients with SLE and 19 healthy controls were detected by the real‐time–quantitative polymerase chain reaction (qPCR). Serum Sema5A levels were increased significantly in SLE patients compared with healthy controls ( P  < 0·001). Elevated levels of Sema5A were correlated positively with 24‐h proteinuria excretion ( r  = 0·558, P  < 0·0001), SLE disease activity index (SLEDAI) ( r  = 0·278, P  = 0·0006) and C‐reactive protein (CRP) ( r  = 0·266, P  = 0·002), but negatively with planet (PLT) ( r  = –0·294, P  = 0·0003) and complement 3 (C3) ( r  = –0·287, P  = 0·0004) in SLE patients. Patients with elevated Sema5A levels showed higher incidence of rash, serositis and nephritis ( P  < 0·05 or P  < 0·001). Patients with decreased PLT, C3 or positive for proteinuria also showed elevated Sema5A ( P  < 0·001 or P  < 0·05). The mRNA ADAM17 was increased in SLE patients and correlated positively with serum Sema5A levels. Our data demonstrated that elevated serum Sema5A in SLE patients correlated with disease activity and are involved in kidney and blood system damage; ADAM17 might be involved in the release of secreted Sema5A. Abstract : Serum Sema5A levels were significantly increased in SLE patients compared with healthy controls Elevated serum Sema5A in SLE patients correlated with disease activity and involved in the kidney and blood system damage.